How Does AI Support Remote Chronic Disease Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
The rising prevalence of chronic diseases such as cardiovascular conditions, diabetes, and respiratory illnesses presents a significant challenge to healthca...
Keywords: Telemedicine and Digital Health; Support; Remote; Chronic; Artificial Intelligence; Healthcare